Reproductive Morbidity in a Village of Kathmandu - Khanal, K; Suvedi, B K (Journal of Nepal Health Research Council, 2014)
Background: Reproductive morbidity has been a less studied area in developing countries. Prevalence of reproductive morbidity and health seeking behavior pertaining to it is little known. To reveal the magnitude, this study was carried out in a village of Kathmandu district. The objective of the study was to find out prevalence of reproductive morbidity and service utilized for them. Methods: A random cross-sectional study was carried out among 200 women of reproductive age years in a village using household survey and structured questionnaire. Results: The study revealed that 72 percent (144) women of reproductive age years have experienced reproductive problem. Gynecological problems contributed for 81 (40%) women and obstetric problems for about 51% of the married women (48 out of 94). Service seeking was found to be very low for gynecological morbidity. Conclusions: Reproductive morbidity was found to be very high in the community. The prevalence of obstetric morbidity was almost in half the study population, whereas gynaecological morbidity was about forty percent among the women of reproductive age group. However, seeking care for reproductive morbidity was low which requires more attention. Â Keywords: gynecological morbidity; Nepal; obstetric morbidity; prevalence; reproductive morbidity; serviceseeking behavior.